2014
DOI: 10.1007/s00268-014-2704-y
|View full text |Cite
|
Sign up to set email alerts
|

Above 5 cm, Size Does Not Matter Anymore in Patients with Hepatocellular Carcinoma

Abstract: Although recurrence rates are high, surgical resection for solitary HCC offers good overall survival. Tumor size was not a prognostic factor. Solitary large HCC >10 cm would be a good candidate for hepatectomy as well as solitary HCC between 5 and 10 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 38 publications
8
75
1
2
Order By: Relevance
“…Large HCCs can potentially be cured through a complete resection [23]. A 5-year OS rate of more than 50% may be achieved through surgery for tumors larger than 5 cm [22]. Postoperative disease-free survival and OS are similar between patients with large and small HCCs when the tumor is solitary [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large HCCs can potentially be cured through a complete resection [23]. A 5-year OS rate of more than 50% may be achieved through surgery for tumors larger than 5 cm [22]. Postoperative disease-free survival and OS are similar between patients with large and small HCCs when the tumor is solitary [24].…”
Section: Resultsmentioning
confidence: 99%
“…Large HCCs are typically associated with a higher incidence of vascular invasion and metastasis and higher histological grades [22]. An increased tumor size is associated with poor postoperative outcomes of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…With advances in surgical resection technique and lower perioperative mortality, survival after liver resection is increasing at many centers. [22][23][24][25][26] This could be particularly important in countries that experience difficulties in obtaining donor livers for transplant. Perhaps the expanded use of resection for HCC and the decreased use of transplant for smaller HCCs could release livers for other transplant indications, such as the presence of a more advanced tumor.…”
Section: Patterns Of Recurrencementioning
confidence: 99%
“…Presence of adverse predictors influence survival. 4,5 The 5-year overall survival rate after liver transplant is about 70%; however, 27% of patients have tumor recurrence after transplant despite fulfilling the Milan criteria. Tumor recurrence is a major limitation on survival.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are several factors, including vascular invasion, satellite nodules, high differentiation grade, and underlying liver disease, that may predict outcomes after hepatic resection; in addition, tumor size is also an important prognostic factor. In a study of patients with solitary HCC, Lim and associates 4 stratified 616 resected patients with solitary HCC according to tumor size: smaller than 5 cm, 5 to 10 cm, and larger than 10 cm. The authors concluded that microvascular invasion, satellite nodules, and a less differentiated tumor were more prevalent in patients with larger tumors.…”
Section: Introductionmentioning
confidence: 99%